2023
DOI: 10.2147/dmso.s388117
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Serum BCAAs are Related to the Improvement in Insulin Resistance in Obese People After a Weight Loss Intervention

Abstract: Background Branched chain amino acids (BCAAs) have been revealed to be closely related to insulin resistance and obesity. This study aimed to investigate if BCAA levels at baseline are related to an improvement in insulin resistance after implementing a weight loss program intervention. Methods Stored blood samples from participants in previous trials were used for BCAA evaluation. Linear regression was used to analyze the relationship between baseline amino acid levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Weight loss could improve BCAA levels, and therefore could contribute to improving insulin sensitivity, but results in the scientific literature are contradictory. Zhang et al found that baseline BCAA levels were associated with the improvement in HOMA-IR in overweight patients after a very low-protein and -calorie diet [ 40 ]. Hernández-Alonso et al observed a significant reduction in leucine and valine levels in overweight and obese patients after a low-glycemic index diet [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss could improve BCAA levels, and therefore could contribute to improving insulin sensitivity, but results in the scientific literature are contradictory. Zhang et al found that baseline BCAA levels were associated with the improvement in HOMA-IR in overweight patients after a very low-protein and -calorie diet [ 40 ]. Hernández-Alonso et al observed a significant reduction in leucine and valine levels in overweight and obese patients after a low-glycemic index diet [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to, numerous studies have highlighted their possible significance in the development and evolution of several pathological problems such as heart failure and metabolic diseases including diabetes and obesity (38). Interestingly, the study of Zhang et al (39) has revealed that the insulin resistance group of obese patients had higher serum levels of BCAAs and AAAs compared with no-insulin resistance group, and that BCAAs levels are associated with alleviation of insulin resistance after weight loss intervention. In addition, another study recently showed a strong association of BCAA levels and nutritional status, impaired glucose tolerance or T2D, and also demonstrated that BCAA levels and their response to, e.g., food intake, are stable over time, re-confirming their utility as potential biomarkers (40).…”
Section: Discussionmentioning
confidence: 99%
“…After a weight loss program intervention, the participants showed an improvement in insulin resistance and lower BCAA plasmatic levels [ 96 ]. Two similar randomized dietary trials, i.e., POUNDS LOST and DIRECT, registered as NCT00072995 and NCT00160108, respectively, showed that both BCAAs and AAAs significantly decreased, with reduced metabolic risk seen in HOMA-IR values in response to weight-loss diet interventions.…”
Section: Therapeutic and Biomarker Potential Of Bcaasmentioning
confidence: 99%